Facilitating Trade in Selected Climate Change Mitigation Technologies in the Energy Supply, Buildings, and Industry Sectors - Steenblik, Ronald (OECD Publishing, 2009)
It is in every country's interest that the deployment of carbon-change-mitigation technologies (CCMTs) be accomplished at the lowest possible cost to society and that their diffusion be rapid. Reducing barriers to trade is one way to accomplish that, especially given that it is unlikely that every country will become proficient in the production of every CCMT. This study provides a preliminary assessment of the significance of tariff and non-tariff barriers to trade in a representative selection of CCMTs chosen from among those that have been identified by the IPCC and the IEA as having a large economic potential for mitigation, are globally traded, and can be easily adapted to national circumstances.
Keywords: Trade